2022
DOI: 10.3390/ijerph192013132
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Job Stress, Role Ambiguity and Work–Life Imbalance on Turnover Intention during COVID-19: A Case Study of Frontline Health Workers in Saudi Arabia

Abstract: The main objective of the present study is to examine the impact of job stress, role ambiguity, work–life imbalance and burnout on employee turnover intention. Moreover, the mediating role of burnout between job stress, role ambiguity, work–life imbalance and turnover intention is also examined. The data collection for this quantitative research was conducted through the “Questionnaire” technique. The questionnaire was developed based on previously established questions available in the literature. The data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
3
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
1
15
3
3
Order By: Relevance
“…In contrast, the multiple extra tasks related to the COVID-19 control measures become a protective factor against stress among primary health workers. This nding is different from other studies, which reported that the increased workload due to the pandemic increased the health workers' stress levels (13,15). Considering the data collection period of our study conducted in mid-2022, in the third year of the COVID-19 pandemic, the primary healthcare workers may have become more resilient.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…In contrast, the multiple extra tasks related to the COVID-19 control measures become a protective factor against stress among primary health workers. This nding is different from other studies, which reported that the increased workload due to the pandemic increased the health workers' stress levels (13,15). Considering the data collection period of our study conducted in mid-2022, in the third year of the COVID-19 pandemic, the primary healthcare workers may have become more resilient.…”
Section: Discussioncontrasting
confidence: 83%
“…There is acceptable evidence of how the COVID-19 pandemic has impacted primary health workers' work and personal lives. Work-life balance is crucial in keeping health workers satis ed with their work conditions to minimize stress and maintain harmony in their workplace (13). Work-life balance among professionals, including health professionals, is the key to better e ciency (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be explained by stress. Previous researchers have found that stress related to COVID-19 can induce turnover intention among healthcare workers [ 59 ]. Moreover, stress can not only have a substantial direct impact on turnover intention but also exert its indirect effect through job satisfaction [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“… 21 Recently, Alblihed and Alzghaibi conducted a study in Saudi Arabia that revealed that during the COVID-19 pandemic, nurses experienced high role ambiguity, which was significantly associated with an increased intention to quit their job. 22 Nurses’ job tasks and responsibilities have risen and become more complicated, leading to an unclear and confusing situation in healthcare sectors. The lack of job roles can adversely affect the quality of service in the nursing profession.…”
Section: Introductionmentioning
confidence: 99%